Power energy management and control for isolated hybrid pv/energy storages microgrid system - Mohd Fauzi, Mohamad Yusof (2022)
Nowadays, renewable energy sources (RES) use in the microgrid environment has gained attention for supplying energy to the end-users and cost-effective investment for a long period with zero CO2 emission. Providing electricity requires voltage transmission from the primary grid to the remote areas, which is sometimes not cost-effective based on the areas' location and give impact towards environment. Simultaneously, since the population keeps growing, it also has a continuous demand for the electricity supply year by year in the rural or remote areas. Therefore, the introduction of an isolated microgrid in remote areas is appropriated. This thesis proposes a new isolated PV microgrid topology at remote areas using PV and battery energy storage with the diesel generator as a backup energy source. The power energy management (PEM) strategy is employed to manage energy sources and control the power flow to the load demands. The objective of isolated PV microgrid is to provide reliable electricity at isolated areas that can minimize the impact of PV solar intermittent factor, environment and work in economic assessment through long-term operation years. Two small PV power plants with different capacities are proposed with two batteries bank of energy storage. First, the approach comes with the analytical formulation sizing of the input sources (PVs and batteries energy storages) based on the proposed isolated microgrid size. The reference current control is proposed for efficiently manage the charging and discharging batteries. The PEM control algorithm is then proposed to optimize the usage of energy sources (PVs and batteries). The PEM also could ensure the operation of the isolated microgrid working efficiently. Furthermore, the battery energy storage characteristics (SoC% and DoD%) are considering to maintaining the life span of the battery. To verify the proposed isolated PV microgrid, a comparison with the traditional isolated PV microgrid topology is presented. The performance such as battery operation, input voltage usage (PVs, batteries, and diesel generator) plotted and compared for detailed analysis in Mathlab Simulink environment. The economic assessment of the proposed isolated PV microgrid and employment PEM are analysed and compared with the traditional isolated microgrid. The results show a significant improvement in terms of isolated microgrid performances that reflected from the intermittent PV power production, management of battery charging/ discharging characteristic and time recovery of speed for the energy storage. The economic assessment is carried out through a long-term operation (based on the life span of the PV degradation). It has shown a reasonable return of investment (ROI) two times faster than the traditional isolated microgrid.